Is hyperthermia the triggering factor for hepatotoxicity induced by 3,4-methylenedioxymethamphetamine (ecstasy)? An in vitro study using freshly isolated mouse hepatocytes - Carvalho, Márcia (2021)
The consumption of 3,4-methylenedioxymethamphetamine (ecstasy; MDMA) may cause hepatocellular damage in humans, a toxic effect that has been increasing in frequency in the last few years, although the underlying mechanisms are still unknown. The metabolism of MDMA involves the production of reactive metabolites which form adducts with intracellular nucleophilic sites, as is the case with glutathione (GSH). Also, MDMA administration elicits hyperthermia, a potentially deleterious condition that may aggravate its direct toxic effects. Thus, the objective of this study was to evaluate the extent of MDMA-induced depletion of GSH, induction of lipid peroxidation and loss of cell viability in freshly isolated mouse hepatocytes under normothermic conditions (37 degrees C) and to compare the results with the effects obtained under hyperthermic conditions (41 degrees C). By itself, hyperthermia was an important cause of cell toxicity. A rise in incubation temperature from 37 degrees C to 41 degrees C caused oxidative stress in freshly isolated mouse hepatocytes, reflected as a time-dependent induction of lipid peroxidation and consequent loss of cell viability (up to 40-45%), although the variations in GSH and GSSG levels were similar to those under normothermic conditions. MDMA (100, 200, 400, 800 and 1600 microM) induced a concentration- and time-dependent GSH depletion at 37 degrees C but had a negligible effect on lipid peroxidation and cell viability at this temperature. It is particularly noteworthy that hyperthermia (41 degrees C) potentiated MDMA-induced depletion of GSH, production of lipid peroxidation and loss of cell viability (up to 90-100%). It is therefore concluded that hyperthermia potentiates MDMA-induced toxicity in freshly isolated mouse hepatocytes.